Sizing optimization of standalone photovoltaic system with hydrogen energy storage using squirrel search algorithm / Aizat Shazni Ahmad Umar - Ahmad Umar, Aizat Shazni (2023)
The current trend in electricity generation is renewable energy technology, with photovoltaic (PV) systems being one of the most promising. PV systems are a type of Distributed Generation (DG) that is commonly used in rural places when grid electricity is unavailable Stand-Alone Photovoltaic (SAPV) systems are frequently employed as electricity delivery systems for rural electrification, system sizing is a major difficulty in their installation. The technical and economic performance of the systems is improved when they are designed properly. Furthermore, when multiple models of system components must be included in the design, sizing becomes computationally expensive. As a result, optimization techniques are widely used in the sizing algorithms for such systems in order to achieve optimal results. The optimization on stand-alone photovoltaic system sizing with hydrogen energy storage considering improved Squirrel Search Algorithms is presented in this thesis.